Cross‐sectional analysis of the association of periodontitis with carotid intima media thickness and atherosclerotic plaque in the Hamburg City health study. (8th June 2022) - Lamprecht, Ragna; Rimmele, David Leander; Schnabel, Renate B.; Heydecke, Guido; Seedorf, Udo; Walther, Carolin; Mayer, Carola; Struppek, Julia; Borof, Katrin; Behrendt, Christian‐Alexander; Cheng, Bastian; Gerloff, Christian; et al.
Abstract: Background: Previous epidemiological studies regarding the association between chronic periodontitis (CP) and carotid intima‐media thickness (cIMT) and subclinical atherosclerosis have been inconclusive. Objective: The aim of this study was to determine whether CP is associated with subclinical atherosclerosis in a large population‐based cohort study conducted in northern Germany (the Hamburg City Health study). Methods: Baseline data from 5781 participants of the Hamburg City Health Study with complete oral health and carotid ultrasound data (50.7% female, mean age: 62.1 ± 8.4 years) were evaluated. A standardized duplex sonography of the carotid artery was performed with measurement of carotid intima‐media thickness (cIMT) and atherosclerotic plaques. Oral health was assessed by recording the decayed, missing, and filled teeth (DMFT) index, clinical attachment loss (CAL), bleeding on probing (BOP), and the dental plaque index (PI). Correlations were tested for statistical significance by means of descriptive statistics and multivariate regression analyses. Results: Moderate and severe CP were associated with the prevalence of cIMT ≥ 1 mm (none or mild CP: 5.1%, moderate CP: 6.1%, severe CP: 10%) and mean cIMT (none or mild CP: 0.72 mm, moderate CP: 0.75 mm, severe CP: 0.78 mm) in bivariate analyses ( p  < .001). Additionally, severe and moderate CP were associated with higher prevalence of carotid atherosclerotic plaques (plaque = yes: none or mild CP: 23.9%, moderate CP: 29%, severe CP: 40.2%, ). After adjustment for age, sex, smoking, diabetes, hypertension, educational level, hypercholesterolemia, and hsCRP, severe CP still correlated significantly with cIMT and the prevalence of cIMT ≥1 mm and/or presence of carotid atherosclerotic plaques. Conclusion: In this study, severe CP was associated with increased cIMT and higher prevalence of carotid plaques independent of common risk factors.